The levels of BMI and patterns of obesity and overweight during the COVID-19 pandemic: Experience from the Iran STEPs 2021 survey - Djalalinia, Shirin; Yoosefi, Moein; Shahin, Sarvenaz; Ghasemi, Erfan; Rezaei, Nazila; Ahmadi, Naser; Rezaei, Negar; Azmin, Mehrdad; Rezaei, Shahabeddin; Nasserinejad, Maryam; Mohammadi, Esmaeil; Haghshenas, Rosa; et al. (Frontiers in Endocrinology, 2022)
Background Obesity and its increasing burden have become an urgent health problem all over the world. Benefiting from a national representative sample, the present study aimed to estimate the distribution of body mass index (BMI) levels and its association with metabolic and lifestyle risk factors in an Iranian adult population by sex, age, and geographical distribution. Methods This study involves a national survey of noncommunicable disease risk factor surveillance (STEPs) in Iran. Through systematic random sampling, in compliance with safety considerations during the COVID-19 pandemic, of the 28,520 adults who gave voluntary consent and included in the study, 27,874 participants completed the questionnaires (step 1), 27,745 individuals were anthropometrically measured (step 2), and 18,119 individuals completed laboratory evaluation (step 3). Anthropometric measurements followed based on standard protocols and by using calibrated instruments. Results In 2021, the national prevalence of normal weight, obesity, and overweight/obesity in ≥18-year-old Iranian adults was estimated at 33.61% (95% CI: 32.99–34.23), 24.96% (24.39–25.53), and 63.02% (62.39–63.65), respectively. Compared to women, Iranian men had a lower mean BMI [25.54 (24.95–26.13 vs. 27.6 (27.07–28.12) kg/m2] (p < 0.001). There was also a significant difference in the national prevalence rate of overweight/obesity [women: 66% (61–71), men: 53% (46–60) (p < 0.001)]. The prevalence of obesity was significantly higher in participants suffering from metabolic and lifestyle risk factors. The study of the geographical extent of obesity and overweight shows that compared to national levels, the highest prevalence of being underweight was seen in the southeastern provinces. On the other hand, the highest prevalence of obesity belonged to the northeastern and central provinces. The highest provincial prevalence of obesity was almost 2.5-fold higher than the lowest provincial prevalence. Conclusion The study reveals a significant difference between the prevalence of obesity in male and female participants and between different regions of the country. These findings will help policymakers, clinicians, and researchers to more accurately estimate the obesity/overweight problem and to implement more effective interventional programs to promote strategies of prevention and control of weight gain.